001 Cognitive function in Friedreich's ataxia patients in Ireland. Issue 3 (9th February 2012) - Albertyn, C; Austin, N; Murphy, R P
Abstract : Introduction: Since the discovery of the causative gene for Friedreich's ataxia (FRDA) in 1996, there have been only a handful of studies looking at cognitive function in these patients, with varying results. We therefore aimed to assess cognitive function in a cohort of FRDA patients in Ireland. Methods: Twenty-seven genetically confirmed FRDA patients were recruited from the national ataxia clinic. Age of onset, duration of symptoms and the Friedreich's ataxia rating scale (FARS) score were documented for each patient. Twenty-eight controls, matched for age, sex and level of education were recruited. The neuropsychological test battery assessed immediate and delayed verbal memory, visuospatial perception, confrontational naming, non-verbal memory, attention and concentration, premorbid intellect, executive function and cognitive speed. The tests were designed to minimise the effects of articulation and motor deficits. Results: Significant differences were found in delayed recognition memory, immediate and delayed verbal recall, visuospatial perception, attention and concentration, executive function and processing speed. No significant differences were seen in immediate recognition memory, premorbid intellect and confrontational naming. The FARS score correlated with duration of symptoms, better performance on verbal recall and visual recognition, but weaker performance on tests of executive function and processing speed. Discussion: Cognitive testing demonstrated slowed cognition, rapid forgetting and poor visuospatial perception in patients compared with controls. These divergent findings may be explained by interruption of the cerebro-cerebellar circuits.